KOMPARASI PEMBERATAN PIDANA TERHADAP PEGAWAI NEGERI SIPIL DALAM TINDAK PIDANA NARKOTIKA : Studi Kasus Perbandingan No.122/Pid.Sus/2020/PN.Pml dan No.87/Pid.Sus/2021/PN.Sdk - Giffari Hayfa Labiba (2022)
Currently, narcotics crimes have penetrated various regions in Indonesia and are widespread in all levels of society including civil servants (PNS). The involvement of Civil Servants in narcotics crimes is very contrary to the program required by the government, namely the National Disciplinary Movement (GDN) in Government Regulation No. 53 of 2010 concerning Civil Servant Discipline. Civil Servants as state servants, appointed by the state and given wages from state finances, have a different position from people who are not Civil Servants. The difference lies in the certain authority granted by the state to civil servants. Therefore, if a Civil Servant is involved in a narcotics crime, then it is appropriate that the criminal sanctions given are more severe than those who are not Civil Servants. Regarding the criminal enforcement rules against Civil Servants involved in narcotics crimes, it has not been regulated in Law No. 35 of 2009 concerning Narcotics. So from this problem, the author made a study on the comparison of criminal charges against Civil Servants in Narcotics Crimes.